Impacts of Land Uses and Droughts on Dissolved Phosphorus Release and Phosphate Solubilizing Bacteria: A Case Study in Son La, Vietnam - Mai Van, Dinh (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 2, 2025)
Climate change is causing an increase in extreme weather events, including droughts in many areas, such as forests and agricultural lands. Drought leads to the dessication of soil microbial cells and nutrient lysis caused by osmotic shock, hence releasing dissolved phosphorus (P) into the soil solution. Drought stress for soils of different land uses can shift the soil microbial community significantly. This study compared the biogeochemical impacts of various land uses under drought stress. Soil samples were collected from the natural forest, corn, and coffee plantations in Son La province, Vietnam. Soils were desiccated up to water content about 2-5%, while controls were kept at 60% soil water holding capacity. The experiment was conducted in a climate chamber at 25 o C for seven weeks in the laboratory. The P release and microbial biomass from natural forest soils, as well as corn and coffee plantation soils were calculated and compared to controls after seven weeks. Soil properties were different among land-use types. Natural forest soil had the highest total P (TP) content, followed by corn and coffee plantation soils, with values of 0.27, 0.27 and 0.09%, respectively. Drought stress increased total dissolved P (TDP) concentrations from 1.0 to 1.17 mg kg -1 in natural forest soil, 0.8 to 0.91 mg kg -1 in coffee plantation soil, and 0.69 to 0.75 mg kg -1 in corn plantation soil. Drought significantly reduced microbial biomass from 1,344 to 526.6 mg kg -1 in coffee plantation soil, from 309.2 to 77.2 mg kg -1 in corn plantation soil and from 250.6 to 100.9 mg kg -1 in natural forest soil. There was a significant difference in carbon mineralization between drought and control conditions. Carbon mineralization in the control samples ranged from 1.04 to 1.08 mg kg -1 , while in the drought experiments, it ranged from 0.64 to 0.67 mg kg -1 . Drought conditions can lead to the death of phosphate solubilizing bacteria. However, the effects of drought on microbial communities and the recovery of these microorganisms require further study.